Developing Sacha Inchi Cultivation in Tabongo Timur Village: An Empowerment Strategy for Food Security and Economic Improvement - Yuszda K. Salimi; Lanto Ningrayati Amali; Umar Sako Baderan; Siti Aisa Liputo; Erni Mohamad (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Tabongo Timur Village, located in the Tabongo Subdistrict, Gorontalo Regency, has significant potential for developing Sacha Inchi as a leading commodity to support food security and enhance the local economy. This empowerment program aims to increase the productivity and quality of Sacha Inchi plants through social, technical, and technological interventions. The program employs the Participatory Rural Appraisal (PRA) approach to actively engage the community in the planning and implementation processes. The methods used include cultivation socialization, technical guidance, product innovation training, and technology implementation for post-harvest processing. The results of the program showed a significant increase in plant productivity and the quality of Sacha Inchi products, achieved through the application of semi-organic cultivation techniques, the use of modern tools, and education related to product innovation. The training provided also improved partners' skills in processing Sacha Inchi into high-value products, such as oil, milk, jam, and snack bars. The discussion shows that this program successfully shifted farmers' mindsets towards better utilization of local potential and strengthened community involvement in productive agricultural activities. Collaboration between the village government, university, and farmer groups was key to the program's success, making Tabongo Timur Village a competitive Sacha Inchi processing center. This program can serve as a model for other villages in empowering local resources to support food security and improve community welfare.